The (Diverse) Company You Keep: Content and Structure of Immigrants' Social Networks as a Window Into Intercultural Relations in Catalonia. (July 2018) - Repke, Lydia; Benet-Martínez, Verónica
This research examines how the social networks of immigrants residing in a European bicultural and bilingual context (Catalonia) relate to levels of adjustment (both psychological and sociocultural) and to bicultural identity integration (BII). Moroccan, Pakistani, Ecuadorian, and Romanian immigrants residing in Barcelona nominated 25 individuals (i.e., alters) from their habitual social networks and provided demographic (e.g., ethnicity), relationship type (e.g., family, friend, neighbor), and structural (who knew whom) information for each of these alters. Even after controlling for individual-level demographic and acculturation variables, the content and structure of immigrants' personal social networks had unique associations with both types of adjustment and with BII. Specifically, the overall degree of cultural diversity in the network and the amount of Catalan (but not Spanish) "weak" ties (i.e., acquaintances, colleagues, neighbors) positively predicted these outcomes. Amount of interconnectedness between local coethnic and Catalan/Spanish alters also predicted sociocultural adjustment and BII positively. Finally, against a "culture and language similarity" hypothesis, Moroccan and Pakistani participants had social networks that were more culturally integrated, relative to Ecuadorians and Romanians. Results from this study attest to the importance of examining actual intercultural relations and going beyond individuals' reported acculturation preferences to understand immigrants' overall adaptation and cultural identity dynamics. Furthermore, results highlight the interplay between interculturalism experienced at the intrapersonal, subjective level (i.e., BII), and at the meso-level (i.e., having culturally diverse networks that also include interethnic ties among alters).